2017
DOI: 10.1002/fsn3.500
|View full text |Cite
|
Sign up to set email alerts
|

Influence of physicochemical parameters on storage stability: Microbiological quality of fresh unpasteurized fruit juices

Abstract: Fresh juices rich in health and nutritional benefits are valued for their fresh flavor, taste, and aroma. These juices' quality however is affected by factors like temperature, light, and microbiological contamination significantly changing physicochemical parameters and storage stability. Physicochemical and microbiological analyses of passion fruit, pineapple, and mango juices in dark and light bottles at 24°C and 4°C were conducted in Kampala, Uganda for 12 days. Physicochemical parameters significantly red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
30
1
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 21 publications
6
30
1
2
Order By: Relevance
“…Dias et al (2011) reported increased vitamin C content of passion fruit juice with the application of bovine bio-fertilizer. On the other hand, °Brix values (9.82 to 9.30) in this study were higher than the values (1.0 to 3.0) recorded by Kaddumukasa (2017) but lower than the value of 12.0 documented by Codex Alimentarius (2005).…”
Section: Discussioncontrasting
confidence: 87%
“…Dias et al (2011) reported increased vitamin C content of passion fruit juice with the application of bovine bio-fertilizer. On the other hand, °Brix values (9.82 to 9.30) in this study were higher than the values (1.0 to 3.0) recorded by Kaddumukasa (2017) but lower than the value of 12.0 documented by Codex Alimentarius (2005).…”
Section: Discussioncontrasting
confidence: 87%
“…Furthermore, there were no significant difference in the population of microorganisms in all fresh samples compares the samples at the middle and the end of storage period in refrigerator or the survival of microorganisms in fresh raisin juice was slightly increased after one and two weeks of storage in refrigerator and these results are in accordance with a previous study done by Elsheikh et al (2014) that investigated the total viable count was nil at zero time of storage and started to increase after 2 months. On teh other hand, this results agrees with results obtained by Kaddumukasa (2017) in the microbiological analyses of passion fruit, pineapple, and mango juices in dark and light bottles at 24°C and 4°C were conducted in Kampala, Uganda for 12 days for juices.…”
Section: Total Bacterial Countssupporting
confidence: 90%
“…Fresh juice not only provides rich nutrients, a pleasurable taste, and an attractive color, but it also has no additives and is pure, natural, and minimally processed. Therefore, in recent years, the consumption of fresh juice has significantly trended upward, and fresh juice is gaining much popularity among customers throughout the world; it has gradually become the new favorite of the beverage industry (2,3). Non-industrial fresh watermelon juice (FWJ) is one of the most common fresh juices in the market; it is an excellent product to quench thirst and relieve the heat in summer and the tropics.…”
mentioning
confidence: 99%
“…For example, a juice shop prepares fresh juice in advance and waits for customers to buy it within a period of time; a housewife prepares too much juice to drink at a single time and drinks the remainder the next day; and a juice shop prepares too much juice to sell in 1 day and then stores the remainder to be sold the next day (6). In addition, compared with industrialized juice, non-industrial fresh juice, including non-industrial FWJ, is usually drank directly after juicing without any sterilization treatment, which results in the problem that bacteria are easily bred and cause microbial contamination during storage and retail (2,(7)(8)(9). In addition, as non-industrial FWJ does not contain any food additives, its sensory index and nutritional and functional indicators will change significantly with the extension of storage time; it is easy to cause sensory deterioration and nutritional loss if stored improperly or for a longer storage time (2,10).…”
mentioning
confidence: 99%